2013
DOI: 10.1038/pr.2013.99
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of levels and patterns of physical activity in preschool children

Abstract: Background:The aim of this study was to examine in detail levels and patterns of physical activity in preschool children and the effects of gender and BMI on this activity. Methods: Two hundred and fifty-three children aged 5 y participating in the Copenhagen Prospective Studies on Asthma in Childhood wore an accelerometer day and night over a 4-wk period. The main outcome measure was level of physical activity using the raw data. A secondary measure was time spent in moderate to vigorous physical activity (MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
3
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
4
26
3
5
Order By: Relevance
“…Our finding of higher PA levels during weekdays compared to weekend days are in line with both a Danish preschool study [14], and a school study [48]. Previous preschool studies from other countries have primarily reported findings consistent with ours [10, 14, 45], or reported no difference between day types [15, 42, 46]. Only a few studies have reported the opposite result, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding of higher PA levels during weekdays compared to weekend days are in line with both a Danish preschool study [14], and a school study [48]. Previous preschool studies from other countries have primarily reported findings consistent with ours [10, 14, 45], or reported no difference between day types [15, 42, 46]. Only a few studies have reported the opposite result, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Only a few studies have investigated variations in PA over all seven days of the week (Monday–Sunday) in preschool-aged children [42, 43], whereas a number of studies have studied differences in PA between weekends and weekdays [10, 14, 15, 42, 4447]. Our finding of higher PA levels during weekdays compared to weekend days are in line with both a Danish preschool study [14], and a school study [48]. Previous preschool studies from other countries have primarily reported findings consistent with ours [10, 14, 45], or reported no difference between day types [15, 42, 46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the assessment of participants’ PA patterns, in line with previous findings preschool boys were slightly more active than girls [21, 58], and children were slightly more active than parents [21, 51]. However, unlike previous pedometer-based studies [58, 59] in children and fathers there were no significant differences between weekdays and weekends PA.…”
Section: Discussionsupporting
confidence: 84%
“…The QOL-fatty food association was sex dependent, with an increased fatty food intake occurring only in girls with low emotional QOL. Indeed, a previous study reported effects of unhealthy food on emotional eating mainly in girls [52] and sex differences have been reported in lifestyle-related reactions [53][54][55]. Other individual differences that might mask an overall QOL effect are psychological eating behaviour (only in emotional eaters), behavioural preferences (only in TV lovers) and biological reactivity [10,[20][21][22].…”
Section: Lifestyle As Outcomementioning
confidence: 98%